SISTEM PENDUKUNG KEPUTUSAN MENGGUNAKAN METODE SAW UNTUK PENILAIAN DOSEN BERPRESTASI (STUDI KASUS DI UNIVERSITAS DEHASEN BENGKULU) - Zulita, Leni Natalia (UNIVED Press, 2013)
One elementin the administration ofhigher educationis theLecturer. Lectureris anacademic staffin charge of implementingthe TriDharma Perguruan Tinggi, whichincludeseducationandlearning, researchanddevelopment of scienceandtechnology, as well ascommunity service. According to Undang-Undang Republik Indonesia No 14 tahun 2005 tentang Guru dan Dosen, Pasal 51 Ayat (1) Butir b, thatLecturersare entitled topromotionsandrewardsaccording totheir academicperformance. Inthis studydesignedadecision support systemfor the assessment ofoutstanding lecturersatDehasenBengkulu university. The method usedisSimple AdditiveWeightingisasimplerankingmethodtoassistin decision making. In theprocess of determiningachievementlecturerusedseveralcriteria:Educational Qualification, Functional, Research, Journals, andDevotioninthe community. Results fromthe systemaremadeistodeterminewhichhas thehighest valueLecturersandtop, andwillserve asoutstandinglecturer.